2010
DOI: 10.1002/jso.21741
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α therapy after curative resection prevents early recurrence and improves survival in patients with hepatitis B virus‐related hepatocellular carcinoma

Abstract: IFN-α therapy after curative resection prevented early recurrence and improved overall survival of patients with HBV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Of the case-control studies that have been reported, 5 are related to hepatitis C [11,12,13] and 2 are related to hepatitis B-related HCC [15,17]. In all of these studies, the recurrence or survival rate was evaluated similarly to RCTs, and significant differences were found in the survival rate with a prolonged duration of IFN administration or the observation period (fig.…”
Section: Low-dose Long-term Ifn Therapy (Ifn Maintenance Therapy) Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Of the case-control studies that have been reported, 5 are related to hepatitis C [11,12,13] and 2 are related to hepatitis B-related HCC [15,17]. In all of these studies, the recurrence or survival rate was evaluated similarly to RCTs, and significant differences were found in the survival rate with a prolonged duration of IFN administration or the observation period (fig.…”
Section: Low-dose Long-term Ifn Therapy (Ifn Maintenance Therapy) Tomentioning
confidence: 99%
“…Also, the recurrence rate of HBV-related HCC as well as the hazard ratio have been reported to be lower in an IFN-treated group than in a non-IFN-treated group [15]. IFN administration has also been reported to increase the overall survival rate [17]. These results suggest that IFN prevents recurrence by suppressing inflammation or by its direct anticancer effect not only in hepatitis C patients but also in patients with hepatitis B.…”
Section: Low-dose Long-term Ifn Therapy (Ifn Maintenance Therapy) Tomentioning
confidence: 99%
“…Much hope for controlling HCC is placed with active prophylaxis before its occurrence. Fortunately, the occurrence and recurrence of HBV-related HCC can be reduced via active prophylaxis using anti-HBV treatments with nucleos(t)ide analogue (NA) and/or IFNa (4)(5)(6)(7)(8)(9)(10). It is, therefore, important to identify the HBV-infected patients who are more likely to develop HCC, allowing timely intervention in those who will benefit most.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect was more prominent in HBeAg-positive Asian patients with chronic hepatitis B [21,22,23,24]. In a recent retrospective case-control study including 317 patients, patients treated with interferon-α had a reduced recurrence rate (p = 0.041) and overall survival (p = 0.009) after resection [25]. In another small-scale RCT [26], adjuvant interferon treatment was only of benefit in advanced-stage HCC after resection.…”
Section: Current Options For the Prevention Of Recurrence After Curatmentioning
confidence: 99%